2016
DOI: 10.1101/040394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying Network Perturbation in Cancer

Abstract: We present a computational framework, called DISCERN (DIfferential SparsE Regulatory Network), to identify informative topological changes in gene-regulator dependence networks inferred on the basis of mRNA expression datasets within distinct biological states. DISCERN takes two expression datasets as input: an expression dataset of diseased tissues from patients with a disease of interest and another expression dataset from matching normal tissues. DISCERN estimates the extent to which each gene is perturbed-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 109 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…Dezso et al developed an algorithm that scores nodes to extract disease-specific subnetworks [25]. However, this method only uses parts of graph information, such as nodes or edges to detect network structure variation, which is not enough to observe network topology variation [26]. IODNE deploys a minimum spanning tree search algorithm and simultaneously scores edges and nodes for selecting subnetworks that are most dysregulated for potential target disease genes.…”
Section: Subnetwork Alignment Score For Priority Targetsmentioning
confidence: 99%
“…Dezso et al developed an algorithm that scores nodes to extract disease-specific subnetworks [25]. However, this method only uses parts of graph information, such as nodes or edges to detect network structure variation, which is not enough to observe network topology variation [26]. IODNE deploys a minimum spanning tree search algorithm and simultaneously scores edges and nodes for selecting subnetworks that are most dysregulated for potential target disease genes.…”
Section: Subnetwork Alignment Score For Priority Targetsmentioning
confidence: 99%
“…Identifying cancer biomarkers has become a crucial way in cancer therapy. Grechkin et al [6] identified topological perturbation in gene regulatory network that included conditional dependencies between candidate regulators and genes and perturbed genes. Yang et al [7] proposed a non-parametric Bayesian framework to identify candidate driver genes in four cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we argue that the latent TF activity inference must be solved jointly and we propose a single, multivariate model. Most previous approaches on TF activity inference calculate each TF's activity individually [7][8][9][10][11][12][13][14] and only aggregate at a later stage. For example, in the popular Gene Set Enrichment Analysis 14 (GSEA), the running sum statistic evaluates each TF's activity individually.…”
mentioning
confidence: 99%
“…We used ten alternative methods that represent a variety of inference and regulation models (Supplementary Note 3). Eight were developed and/or previously used to estimate regulatory activity [7][8][9][10][11][12][13][14] . We also included two differential expression methods to test the effectiveness for searching for an increase in the expression of the TF itself as a marker of its activity: ANOVA as a canonical differential expression analysis method 11 , and sleuth as a state-of-the-art DE method 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation